Faktor yang Mempengaruhi Harga Saham: Bukti Empiris dari Indonesia - Putro, Guruh Marhaenis Handoko; Astuti, Suryani Yuli; Masadah, Ninik; Imawan, Amrizal; Febrianti, Devi; Megasyara, Ira; Wany, Eva (Journal of Culture Accounting and Auditing, 2023)
The financial ratios of liquidity, profitability, solvency, activity, and basic earning ratio on share prices are the financial ratios used in this study to analyze the financial performance of the real estate and property sectors. It employs multiple linear regression. Purposive sampling, a quantitative strategy, is used in this study with 69 samples that contain secondary data from the 2019–2021 financial statements. SPSS 26 is the analytic tool used. The findings indicate that while rentabilitas is important and influences share prices, liquidity, solvency, profitability, and activity have little bearing on share prices. The researcher reveals this occurrence by using signalling theory, which strengthens the findings.